Safety issues of antiarrhythmic therapy for atrial fibrillation - I.I. Reznik; Ya.G. Bozhko (LLC "MEDIAFORMAT", 2024)
The article discusses the safety of antiarrhythmic therapy for atrial fibrillation in the light of the development of cardiac and non-cardiac side effects, the presence of drug-drug interactions of antiarrhythmic drugs in the near (with anticoagulants) and far circle. The features of the choice of antiarrhythmic therapy for the prevention of relapses of atrial fibrillation, restoration of sinus rhythm, as well as heart rate control are presented, and aspects of the tactics of managing these patients are highlighted.